Partial epineural burying of nerve grafts with different sizes next to or distant from neurorrhaphys site: histological and electrophysiological studies in rat sciatic nerves - Cunha,Marco Túlio Rodrigues da (2001)
The aim of the present study was to compare and correlate histologically and electromyographically the effects of partial epineural burying of sural nerve segments in sectioned and sutured rat sciatic nerves. Sixty adult male Wistar rats were operated on 3 groups: Group 1, sural nerve graft, 9mm long, placed next to neurorrhaphy; Group 2, sural nerve graft, 9mm long, buryied 10mm distant from neurorrhaphy; Group 3, sural nerve graft, 18mm long, set next to neurorrhaphy. The morphological features were examined at light microscope after 3 months in 45 rats. The elements observed were: vascularization, vacuoles in nerve fibers, mastocytes and inflammatory infiltrate. The morphometry was made after 6 months in 15 rats from Group 1, 2 and 3, measuring external nerve fiber diameters and counting myelinated nerve fibers/mm². The electrophysiological study was perfomed after 6 months, registering maximum amplitude and frequency of EMG pontentials, at rest, in extensor digitorum longus muscle. Group 3 rats presented sciatic nerves better conserved morphologically and mean external nerve fiber diameters greater than those from Groups 1 and 2. There were no significant differences in density of nerve fibers/mm², and in the electrophysiological study in rats from Group 1, 2 and 3. The epineural burying of sural nerve grafts with greater length and placed next to the neurorrhaphys site had a significantly better regeneration of the histological features than the smaller ones distant from neurorrhaphy.